NATURE AND ART AFTER CORONA, NEW POTENTIALITIES AND FUTURE MISFORTUNES - Porwal, Tina (ShodhKosh: Journal of Visual and Performing Arts, 2020)
Much has already been written about Covid-19, but now we should get used to living with it because Corona is not going to leave our lives so easily. We should now practice living with it. As soon as the lockdown ends, we have to defend ourselves and our family and at the same time run our business smoothly. Now we should learn how to keep our family away from the corona, and stay unconnected, follow social distance, etc. Now this is our life for some time to come. We have to make ourselves so strong that the corona cannot spoil us. Over time, we will get used to living with it. An artist must also change his mind and accept the coming change.